Exertional heat stroke in sport and the military: epidemiology and mitigation. Issue 10 (14th September 2022) - Périard, Julien D.; DeGroot, David; Jay, Ollie
Abstract : New Findings: What is the topic of this review? Exertional heat stroke epidemiology in sport and military settings, along with common risk factors and strategies and policies designed to mitigate its occurrence. What advances does it highlight? Individual susceptibility to exertional heat stroke risk is dependent on the interaction of intrinsic and extrinsic factors. Heat policies in sport should assess environmental conditions, as well as the characteristics of the athlete, clothing/equipment worn and activity level of the sport. Exertional heat stroke risk reduction in the military should account for factors specific to training and personnel. Abstract: Exertional heat illness occurs along a continuum, developing from the relatively mild condition of muscle cramps, to heat exhaustion, and in some cases to the life‐threatening condition of heat stroke. The development of exertional heat stroke (EHS) is associated with an increase in core temperature stemming from inadequate heat dissipation to offset the rate of metabolically generated heat. Susceptibility to EHS is linked to the interaction of several factors including environmental conditions, individual characteristics, health conditions, medication and drug use, behavioural responses, and sport/organisational requirements. Two settings in which EHS is commonly observed are competitive sport and the military. In sport, the exact prevalence of EHS is unclear due to inconsistent exertional heat illness terminology, diagnostic criteria and data reporting. In contrast, exertional heat illness surveillance in the military is facilitated by standardised case definitions, a requirement to report all heat illness cases and a centralised medical record repository. To mitigate EHS risk, several strategies can be implemented by athletes and military personnel, including heat acclimation, ensuring adequate hydration, cold‐water immersion and mandated work‐to‐rest ratios. Organisations may also consider developing sport or military task‐specific heat stress policies that account for the evaporative heat loss requirement of participants, relative to the evaporative capacity of the environment. This review examines the epidemiology of EHS along with the strategies and policies designed to reduce its occurrence in sport and military settings. We highlight the nuances of identifying individuals at risk of EHS and summarise the benefits and shortcomings of various mitigation strategies.